Lacan and Adolescence: The Contemporary Clinic of the “Sexual Non-rapport” and Pornography - Ouvry, Olivier (Frontiers in Psychology, 2018)
This article explores two clinical phenomena – pornography and conspiracy thinking – that are highly relevant today and can be observed specifically among adolescent boys in the early stages of post-puberty: conspiracy thinking and the viewing of pornographic videos. It shows that the Lacanian concepts of the Real (of puberty) and the sexual non-rapport help us understand the psychopathological aspects of these two phenomena. Watching pornographic material becomes equivalent to a conspiracy theory about the sexual non-rapport; both in fact deny the effect of what puberty introduces as radically new.